(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
This study deals with the design and the additive manufacturing of a patient-specific wrist orthosis including integrated functional parts. The orthosis should meet the requirements for a defined clinical picture and at the same time represent the advantages of additively manufactured medical devices.